Clinical characteristics of T790M-positive lung adenocarcinoma after resistance to epidermal growth factor receptor-tyrosine kinase inhibitors with an emphasis on brain metastasis and survival. (July 2018) - Joo, Jin Woo; Hong, Min Hee; Shim, Hyo Sup
Highlights: T790M mutation is common in tumors harboring EGFR exon 19 deletion compared to L858R. Patients who had a T790M mutation and received osimertinib treatment had the best prognosis. Treatment with osimertinib is associated with prolonged brain metastasis-free survival. Abstract: Objectives: We aimed to investigate the clinical characteristics of lung adenocarcinomas with acquired EGFR T790M mutation focusing on brain metastasis and survival. Materials and methods: Our study included patients who had lung adenocarcinoma harboring EGFR mutation at 1st biopsy and then underwent 2nd biopsy after resistance to first- or second-generation epidermal growth factor receptor-tyrosine kinase inhibitors (EGFR-TKIs). Statistical analyses were performed to examine the associations between clinicopathologic features of lung adenocarcinoma and presence of acquired T790M mutation. Results: A total of 111 patients were identified. Of these, 58 patients (52.3%) had acquired T790M mutations. Osimertinib was used in 29 patients (26.1%) after resistance to first- or second-generation TKIs. The T790M mutation was more frequently found in patients with exon 19 deletion than in those with L858R mutations (p = .026) and in patients who had longer treatment duration with EGFR-TKI (p = .0398). Multivariate analysis revealed that exon 19 deletion (p = .003) were independently associated with T790M mutation. Patients with acquired T790M mutation showed a longer progression-free survival. In addition, patients who had T790M mutation or who received osimertinib treatment had a longer overall and post-progression survival than patients who did not. Brain metastasis-free survival was also longer in the T790M-positive group or osimertinib-treated group among patients who had no brain metastasis at the time of diagnosis. Osimertinib treatment was independently associated with longer overall, post-progression, and brain metastasis-free survival. Conclusion: The status of acquired T790M mutation was correlated with exon 19 deletion and longer progression-free survival to first- or second-generation EGFR-TKIs. A third-generation EGFR-TKI, osimertinib, was strongly associated with brain metastasis-free survival as well as other survival indicators in patients with EGFR -mutant lung adenocarcinoma.